GURU MADRASAH YANG PROFESIONAL DAN MODERAT DI ERA DISRUPSI - Darwin (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2021)
Entering the 21st century the challenges of madrasa teachers are getting heavier, the demands of adjusting professionalism with technological development cannot be avoided. Rapid changes caused by technological advances have caused some disruption, one of which is the role of teachers as educators who have begun to be replaced by technology. The picture of professional teachers in the era of disruption is not only based on the ability to apply the competencies required by law. The purpose of writing this article is as a means to convey the writer's idea about the description of professional and moderate madrasa teachers in the era of disruption, knowing the problems and the efforts that must be made by madrasa teachers in the era of disruption. The results of the analysis show that (1) Madrasa teachers must be able to develop their professionalism which is not limited to the competencies required by the law, face the impact of technological developments that allow for disunity, the madrasa teachers are required to be moderate and transmit to students (2) ) Teacher professionalism in the era of disruption is not only related to pedagogical competence, professionalism, social and personality, but also the ability to apply Islamic values in life, another professionalism that is demanded is the ability to integrate science and the Qur'an.